Mauʿiẓah-yi ḥasanah - Naḏīr Aḥmad (Maǧlis-i Taraqqī-i Adab, 2008)
Collection of letters of advice from the author to his son, Bashiruddin Ahmad
Keywords: Briefsammlung; Aḥmad; Bashīruddīn; Naẕīr Aḥmad 1836-1912